Rosai-Dorfman disease of the oral cavity - Charfeddine, Abir; Omami, Mounir; Garma, Marwa; Bellalah, Ahlem; Sioud, Sameh; Selmi, Jamil (Autopsy and Case Reports, 2023)
First described by J Rosai and R F Dorfman in 1969, Rosai-Dorfman disease (RDD) is a benign, self-limiting histiocytosis of unknown etiology. It is usually seen in the first two decades of life. The most frequent clinical presentation is painless, bilateral cervical lymphadenopathy accompanied by fever, weight loss, and an elevated ESR. However, RDD without nodal involvement is extremely rare, and the most common extranodal location is the head and neck region, mainly affecting the nasal cavity, pharynx, and paranasal sinuses. Oral location of RDD is occasional; according to our knowledge, only 17 cases of oral Rosai-Dorfman disease without lymph node involvement have been found in the literature. Because of the rarity of these isolated oral presentations, the clinical and radiological aspects need to be more studied. This article aims to present a rare case of oral Rosai-Dorfman disease without nodal involvement, detail the clinical and radiological signs, and the treatment strategy used in our patient.